Homologasi Penundaan Kewajiban Pembayaran Utang (PKPU) Sebagai Upaya Preventif Terjadinya Pailit : Studi Putusan Mahkamah Agung No.137K/Pdt.Sus-PKPU/2014 - Maranatha Purba; Sunarmi Sunarmi; Bismar Nasution; Keizerina Devi (Universitas Sumatera Utara, 2019)
Abstract. Homologation is the endorsement by the judge of the peace agreement between the debtor by the creditor to end the bankruptcy. Peace (akkoord) in phases this phase is PKPU is most important, because in the debtor will offer peace plan peace were to creditors. The possible existence of peace in the restructuring of debts the debtor. If peace is approved by the creditors, then the PKPU by-law will end. Peace is one of legal efforts to resist he did bankruptcy against the debtor. Peace in the process of bankruptcy is often referred to with the term